Chemical composition of Pacific manganese nodules and crusts analyzed at Scripps Institution of Oceanography using atomic absorption spectrophotometry (AAS) - Fisk, Mary B; Frazer, Jane Z (PANGAEA, 2022)
16 manganese nodules and crusts from 11 sites in the Pacific Ocean were analyzed at Scripps Institution of Oceanography using atomic absorption spectrophotometry (AAS). Samples were ground to < 74 microns, pressed into pellets and dried at 110 Degrees Centigrade.
Keywords: Geochemistry; manganese micronodule; manganese nodule; ocean; sediment